From Waste to Wealth: Community Service for Sustainable Furniture Production - Komang Widhya Sedana Putra P; Wayan Sri Maitri (Program Studi Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2024)
The PKM activity was carried out in Dalung, Badung, Bali. It adopts the use of reclaimed wood in furniture production. The background of this activity is that UMKM (Micro, Small, and Medium Enterprises) face an obstacle in their efforts to manage the cost of production and increase product quality. High dependence on new wood raises production costs, and as a result, it confines profitability. The program was designed to enhance the operational skills of UMKM operators to process reclaimed wood efficiently for lower cost production and high-quality final products.Participatory approaches were applied, followed by technical training sessions and direct production assistance. The beneficiary activities included identification of problems within a specific context, practical training in techniques for processing reclaimed wood, and managerial skills that aim to improve efficiency in resource use. The activities involved three main stages: socialization and problem identification, technical training, and tutoring during the course of production.The results were fairly impressive: the reduction of production costs by 25-30% due to the use of reclaimed wood, improvement of technical skills of participants, and enhanced product quality to meet local consumer standards. The program promoted active involvement in the community as well, because the participants expressed great interest in the application of the techniques learned. The overall outcomes of PKM helped not only to empower local UMKM but also to train people in sustainable practices within the production of furniture. Therefore, it placed an emphasis on the use of local resources and on continuous training as a stimulus for grass-roots economic growth.